Implementasi Manajemen Pembiayaan Pendidikan di Madrasah Aliyah Swasta Pedesaan: The Implementation of Educational Finance Management in Rural Private Madrasah Aliyah - Karimah, Aida; Nugraha, Mulyawan Safwandy (Risalah Kharisma, 2023)
This research aims to describe the supervision of the education budget in terms of the sources and allocation of the education budget at MAS Al Ihya Cianjur for the 2022 fiscal year. The number of informants was 6 people. The data collection methods used were interviews, observation and documentation. Data analysis is a descriptive qualitative approach with the main components, namely data reduction, data presentation and drawing conclusions. Checking the validity of the data uses triangulation techniques. The results of the research show that the source of education funding comes from various sources amounting to IDR 287,120,000.00, the allocation for school development is IDR 287,120,000.00. Implementation of education financing starts from planning with reference to the Madrasah Budget Revenue Plan (RAPBM). Costs that do not match their realization are made into a new recapitulation. The most expenditure is used for honorarium for educators and education staff amounting to IDR 87,450,000.00. Supervision and accountability are carried out by the Ihya Ulumiddin Foundation, the School Committee, and the Cianjur Regency Penmad.